THE ROLE AND APPLICATION OF IDIOMS IN SHAPING NARRATIVE AND CHARACTER DEVELOPMENT IN FICTION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the significance of idioms in fictional literature, focusing on their role in narration and character development. Idioms enrich the narrative voice, contribute to the authenticity of dialogues, and offer deeper insight into the psychological and cultural dimensions of characters. By analyzing examples from classical and contemporary fiction, the article highlights how idioms reflect personal and regional identities and support immersive storytelling. The findings suggest that the effective use of idioms can greatly enhance literary style, reader engagement, and character relatability.